2005
DOI: 10.1186/1477-7827-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Rats with steroid-induced polycystic ovaries develop hypertension and increased sympathetic nervous system activity

Abstract: Background: Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder associated with ovulatory dysfunction, abdominal obesity, hyperandrogenism, hypertension, and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 54 publications
8
27
0
Order By: Relevance
“…While L had no significant effect from this perspective, in the EV group we observed an increased level of fasting glycemia. This result was consistent with Letrozole vs estradiol valerate PCOS in rats our previous study (Dȃneasȃ et al 2014), but contrary to the results obtained in literature (Stener-Victorin et al 2005, Dikmen et al 2012. Slightly elevated glycemic levels are able to promote mitochondrial reactive oxygen species (ROS) production (Nishikawa et al 2000).…”
Section: Discussionsupporting
confidence: 83%
“…While L had no significant effect from this perspective, in the EV group we observed an increased level of fasting glycemia. This result was consistent with Letrozole vs estradiol valerate PCOS in rats our previous study (Dȃneasȃ et al 2014), but contrary to the results obtained in literature (Stener-Victorin et al 2005, Dikmen et al 2012. Slightly elevated glycemic levels are able to promote mitochondrial reactive oxygen species (ROS) production (Nishikawa et al 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Women with PCOS have increased sympathetic activity 28 . Manneras and colleagues and Stener-Victorin also found that sympathetic activity was increased in a Wistar model of PCOS 12, 16 . It is not clear whether increased sympathetic activity contributes to the elevated blood pressure in HAF rats..…”
Section: Discussionmentioning
confidence: 88%
“…Models of estradiol valerate-induced PCO have been described, but plasma testosterone levels were lower in the treated rats than controls, and the treated rats did not exhibit insulin sensitivity 12 . Shi and colleagues also reported that the JCR:LA-cp rat develops features of PCOS, such as obesity, insulin resistance, elevated serum testosterone levels, but this model has a defect in the ObR gene leading to loss of leptin receptor function 13 .…”
mentioning
confidence: 99%
“…Furthermore, it is clear that both androgenic and oestrogenic mechanisms are involved in the programming of the PCOS phenotype as in the prenatally androgenised sheep model testosterone, but DHT does not induce polycystic ovaries and abnormal antral follicle morphology and does not increase follicle activation (West et al 2001, Smith et al 2009). In saying this, further support for AR-mediated actions playing a predominant role in the manifestation of PCOS traits comes from the findings that exposure of rats to E 2 valerate can induce anovulation and polycystic ovaries, but it fails to provoke the breadth of features induced by androgens including LH hypersecretion, hyperandrogenism, obesity and alterations in glucose and insulin sensitivity (Brawer et al 1978, Stener-Victorin et al 2005. Furthermore, differences in the timing of the elevated androgen exposure have recently been put forward as a key determinant in the development of various characteristics of PCOS.…”
Section: Dihydrotestosteronementioning
confidence: 99%